2012
DOI: 10.5216/rpt.v41i1.17742
|View full text |Cite
|
Sign up to set email alerts
|

Dermatite cercariana por esquistossomatídeos de aves: É possível a ocorrência de casos no Brasil?

Abstract: A dermatite cercariana causada por larvas de esquistossomatídeos de aves tem sido considerada uma enfermidade emergente. Embora ainda não haja relato de casos no Brasil, algumas espécies destes trematódeos já foram encontradas em aves e os potenciais hospedeiros intermediários (moluscos) estão amplamente distribuídos pelo país. Em razão da dificuldade de diagnóstico clínico diferencial da dermatite causada por larvas de Schistosoma mansoni, é possível que outras dermatites cercarianas sejam negligenciadas em n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
0
4
0
2
Order By: Relevance
“…Cercarial dermatitis 42 , which is considered an emerging disease, may be occurring in the study area because Ampullariidae and Planorbidae specimens have been found harboring Brevifurcate apharyngeate cercaria in the municipalities of Alto Paraguai, Poconé and Nobres 43 . According to Horák and Kolárová 44 , the dispersal of bird schistosomes to new regions and an increased availability of snail hosts, together with the use of new water reservoirs for recreational purposes, may contribute to a higher number of outbreaks of cercarial dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Cercarial dermatitis 42 , which is considered an emerging disease, may be occurring in the study area because Ampullariidae and Planorbidae specimens have been found harboring Brevifurcate apharyngeate cercaria in the municipalities of Alto Paraguai, Poconé and Nobres 43 . According to Horák and Kolárová 44 , the dispersal of bird schistosomes to new regions and an increased availability of snail hosts, together with the use of new water reservoirs for recreational purposes, may contribute to a higher number of outbreaks of cercarial dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, thus far, B. straminea that are naturally infected with S. mansoni have not been observed in the Pampulha reservoir. In contrast, the cercariae of avian schistosomes, which may be involved in cases of cercarial dermatitis in humans, were recently reported in B. straminea collected from this reservoir 31 .…”
Section: Malacologicalmentioning
confidence: 83%
“…In the Brazilian context, other schistosomes are not of great relevance to human health, as only S. mansoni causes schistosomiasis in Brazil. Avian schistosomes have been reported to cause cercarial dermatitis in the northern hemisphere, but this condition has not been reported thus far in Brazil [ 57 59 ]. As an alternative means of avoiding inconclusive results, we suggest that the visual inspection of reaction tubes by the naked eye should be prioritized, instead of running the LAMP products in gels.…”
Section: Discussionmentioning
confidence: 99%